THE PERFORMANCE OF LAND AFFAIR OFFICE IN SERVING LAND CERTIFICATE: DESCRIPTIVE STUDY TOWARD THE SERVICE OF LEASE HOLD LAND SHIFT CERTIFICATION IN LAND AFFAIR OFFICE OF BARRU REGENCY - Hj. Aidah (Meraja journal, 2020)
[Full Paper] to pdf Copyright (c) 2020 Meraja journal